The role of kisspeptin in the pathogenesis of a polycystic ovary syndrome - Aasif Adiba; Alam Roshan; Ahsan Haseeb; Khan Mohammad Mustufa; Khan Arshiya; Khan Saba (Endocrine Regulations, 2023)
Hypothalamic-pituitary gonadal (HPG) axis is responsible for the development and regulation of the female reproductive system. In polycystic ovary syndrome (PCOS), there is a disturbance in the HPG axis. Kisspeptin, a neuropeptide produced by the KISS1 gene, plays a vital role in the regulation of HPG axis by binding with its receptors KISS1R/GPR54, and stimulates gonadotropin secretion from the hypothalamus into pituitary to release luteinizing hormone (LH) and follicle stimulating hormone (FSH). Polymorphisms or mutations in the KISS1 gene can cause disturbance in the kisspeptin signaling pathway and is thought to disrupt HPG axis. Altered signaling of kisspeptin can cause abnormal secretion of GnRH pulse, which leads to increased LH/FSH ratio, thereby affecting androgen levels and ovulation. The increased levels of androgen worsen the symptoms of PCOS. In the present article, we review the molecular physiology and pathology of kisspeptin and how it is responsible for the development of PCOS. The goal of this review article is to provide an overview and metabolic profile of kisspeptin in PCOS patients and the expression of kisspeptin in PCOS animal models. In the present article, we also review the molecular physiology and pathology of kisspeptin and how it is responsible for the development of PCOS.